The Plight of Bolivian Coca Leaves: Bolivia's Quest for Decriminalization in the Face of Inconsistent International Legislation - Abraham Kim (Washington University Global Studies Law Review, 2014)
Part One will discuss the importance of the coca leaf to Bolivia and give a brief background of the forced eradication and anti-drug efforts that Bolivia has faced. Part Two will explore the various relevant United Nations legislation, Bolivia’s relevant domestic laws, and the troublesome conflicts these regulation attempts have presented. Part Three will briefly discuss the monist and dualist systems of international law, and how Bolivia’s monist system approaches the coca leaf issue. Lastly, Part Four will propose a number of suggestions on how Bolivia could alternatively approach this dispute, how the United Nations could help disentangle the conflicting legislation, and ways that further coca leaf concessions could benefit Bolivia and the world while also potentially influencing other drug legislation.
Keywords: coca; Bolivia; coke; cocaine; narcotics; drug trafficking; United Nations; war on drugs; drugs; criminalize; decriminalization; medicine